Effects of interdependence and social interaction-based person-team fit - David J. Glew (Administrative Sciences, 2012)
The match between employees and their vocations, jobs and organizations has been the focus of the majority of past person-environment fit research. The compatibility between individuals and their work team environments is a more recently recognized, but much less studied, type of fit. Person-team fit is conceptualized here along two fundamental dimensions of team environments: interdependence and social interaction. Results from a study involving 209 cross-functional team members indicate that person-team fit has an impact on satisfaction, commitment, trust and performance.
Keywords: 350; person-team fit; work teams; interdependence